Methodologies for the analysis of the still image in advertising documents: review and applications - Acal Díaz, Inmaculada (Revista General de Información y Documentación, 2015)
The purpose of this article is to propose a methodology to analyse the advertising documents content in still image. First of all, it defines advertising documents, its features as a document, its receivers, and the determinants of its analysis. In the second place, it emphasises the important elements and the recovery of these documents. In the third place, it describes the Lasswell and Chaves model, the rhetoric and the models of Barthes, Durand and Ricarte for the analysis of advertisement documents before we explain in detail the proposed method for the content analysis. Finally, the methodological template proposal is presented and its functionality for the abstract and for the assignment of keywords is demonstrated by making use of it in an example.